Effects of Work-Life Balance and Burnout Towards Employee Performance Through Job Satisfaction as an Intervening Variable : On Student Crew Wedding Organizer in Tasikmalaya - Dwi Amellia, Savira; Nur Fahmi Mufreni, Alfin; Ramadhani, Indi (Ann Publisher, 2023)
This study aims to determine and analyze the effect of work-life balance and Burnout on employee performance through job satisfaction in wedding organizer student crews in Tasikmalaya. Many students are enthusiastic about participating in this open recruitment, making work as a wedding organizer the latest trend to be used as a busyness. Wedding organizers in Tasikmalaya City are predicted to continue to grow along with the high number of people holding wedding receptions. It can be realized that by working, students will get experience, skills, and a general and accurate picture of work. However, with all these work activities, there will be concerns that students will be complacent and forget their study obligations. The research method used was a survey method. Does the data obtain through questionnaires to 117 respondents taken from students working part-time as crew wedding organizers? Sampling using a census and the process of analysis used in this study is path analysis. Based on the research results, it is known that job satisfaction mediates work-life balance and Burnout on employee performance. In this study, work-life balance is good, and work burnout is low, which means the employee's Performance is good.